The approach of Imam Ismail bin Muhammad Al-Ajlouni in his book (Kashf Al-Khafaa) - Maher Muhammed Fattah,; Khaled Hamada Saleh, (Islamic Sciences Journal, 2024)
ABSTRACT There are hadiths going around on people’s tongues at all times, and they mention them as proverbs and wisdom, some of them are true, some are weak, and some are false fabricated, and most of this is promoted by the public. The matter, and showed them the truth from error, and among these books is the book “Unveiling the Hidden and Removing the Confusion about the Famous Hadiths on People’s Sunnah” by Al-Ajlouni. In my research, I liked to study the approach of this great scholar in his valuable book, and he collected in his book “Kashf al-Khafaa” the largest possible number of hadiths that are well-known on the tongues of people, and discussed them with an objective scientific discussion, indicating in them the degree of hadiths, relying on the science of wounding and ta’deel for men The hadiths mentioned by the scholar Al-Ajlouni in his book amounted to three thousand and two hundred hadiths, between true, good, weak, and fabricated.